Pengaruh Pemanfaatan Bahan Ajar Berbasis Video pada Mata Pelajaran Sejarah Kelas X di SMK Mahisa Agni Gunungkidul - Beny Faif Rahardhiyato; Victor Novianto (UM Purwokerto Press, 2023)
History is one of the subjects that plays a significant role in shaping an individual's identity and perspective towards the world. However, most students struggle to understand and appreciate history. Innovative and engaging learning methods can be achieved through the use of multimedia technology such as videos. In this article, researchers will discuss a meta-analysis of how the use of videos about historical places around the school can enhance students' understanding of history. This meta-analysis collects and analyzes the results of several previous studies on the use of videos to improve students' historical understanding. The results of the analysis show that the use of videos in history education can enhance students' understanding of history and help them increase the value and meaning of historical events. Furthermore, the use of videos about historical places around the school can also help students better understand history and increase their pride in their living environment. Videos can also help students better understand the social, cultural, and political contexts of historical places. However, the use of videos in history education also has some weaknesses, such as the possibility of students becoming bored if the videos watched are too long or uninteresting. Therefore, appropriate video design and usage are necessary in the learning context. In conclusion, the use of videos about historical places around the school can be an effective innovative learning method to enhance students' understanding of history. Appropriate videos can help students better understand historical contexts, increase pride in their environment, and appreciate the values and meanings of historical events. Therefore, multimedia technology such as videos can be an interesting and effective alternative in history education.